2017
DOI: 10.1128/mcb.00013-17
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Myeloid Differentiation with Reduced Cell Cycle Progression by PU.1 Induction of MicroRNAs Targeting Cell Cycle Regulators and Lipid Anabolism

Abstract: During macrophage development, myeloid progenitor cells undergo terminal differentiation coordinated with reduced cell cycle progression. Differentiation of macrophages from myeloid progenitors is accompanied by increased expression of the E26 transformation-specific transcription factor PU.1. Reduced PU.1 expression leads to increased proliferation and impaired differentiation of myeloid progenitor cells. It is not understood how PU.1 coordinates macrophage differentiation with reduced cell cycle progression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…BN cells are myeloid precursor cells that are impaired for differentiation as a consequence of low PU.1 expression, and proliferate continuously in culture in response to granulocyte-macrophage colony-stimulating factor (GM-CSF) (26, 32). We previously showed that induction of PU.1 in inducible BN (iBN) cells resulted in downregulation of Acly encoding ATP Citrate Lyase (ACL), and that this regulation was likely indirectly mediated through induction of microRNAs (27). BMS303141 (BMS) is an effective inhibitor of ACL activity (33) and was sufficient to inhibit cell cycle progression in cultured BN cells (27).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…BN cells are myeloid precursor cells that are impaired for differentiation as a consequence of low PU.1 expression, and proliferate continuously in culture in response to granulocyte-macrophage colony-stimulating factor (GM-CSF) (26, 32). We previously showed that induction of PU.1 in inducible BN (iBN) cells resulted in downregulation of Acly encoding ATP Citrate Lyase (ACL), and that this regulation was likely indirectly mediated through induction of microRNAs (27). BMS303141 (BMS) is an effective inhibitor of ACL activity (33) and was sufficient to inhibit cell cycle progression in cultured BN cells (27).…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that induction of PU.1 in inducible BN (iBN) cells resulted in downregulation of Acly encoding ATP Citrate Lyase (ACL), and that this regulation was likely indirectly mediated through induction of microRNAs (27). BMS303141 (BMS) is an effective inhibitor of ACL activity (33) and was sufficient to inhibit cell cycle progression in cultured BN cells (27). We set out to determine if supplementation of BN cells with acetyl-CoA could rescue BMS inhibition of cell cycle.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations